Spatiotemporal Characteristics of Vegetation Cover and Climate Driving Factors in Sichuan Province from 2000 to 2020 - Xin Yu; Sun Mengxin; Zhang Yue; Zhong Dingjie; Yang Cunjian (Shuitu baochi tongbao, 2022)
[Objective] The vegetation change and important climate factors influencing fractional vegetation coverage (FVC) in Sichuan Province were analyzed in order to provide theoretical support for the sustainable development of natural resources in this area. [Methods] Based on the MODIS-NDVI dataset for Sichuan Province from 2000 to 2020, FVC for the study area from 2000 to 2020 was statistically analyzed, and its spatiotemporal variation characteristics and relationships with climate factors were analyzed. [Results] ① The FVC of Sichuan Province tended to be stable, and the average FVC value was about 0.50. ② FVC exhibited obvious spatial heterogeneity. FVC in the east was higher than in the west, and presented an increasing spatial distribution pattern from northwest to southeast. ③ The areas with high FVC in Sichuan Province accounted for about 70% of the total area, and the overall vegetation status was good. There were signs of slow growth in FVC over time. ④ FVC changes in the study area were positively and negatively correlated with air temperature and precipitation, and the area proportions were close to each other. ⑤ The driving forces of FVC change in Sichuan Province were mainly non-climate factors, and the area driven by climate factors accounted for 21.17% of the total area. [Conclusion] Sichuan Province has complex topography. The good climatic conditions, vigorous vegetation growth, and stable FVC experienced over a period of many years has maintained the ecological environment of the middle and upper reaches of the Yangtze River. In the future, Planners and officials should give more attention to the impacts of human activities FVC, and actively build an ecological barrier in the middle and upper reaches of the Yangtze River.